Modelling land use and land cover changes in Portugal: a multi-scale and multi-temporal approach - Meneses,Bruno M. (2018)
Portuguese territory has experienced relevant land use and land cover changes (LUCC) in recent decades. The revision of existing land use and land cover (LUC) datasets and the production of new datasets have allowed us to better understand LUCC over time. This study furthers that analysis by using the most recent LUC datasets, which cover the entirety of the Portuguese continental area from 1990 to 2012 and presents innovative knowledge that aids in the understanding of LUC dynamics within that period. This study shows that the trends that have induced spatial variations within different LUC classes have changed over time, revealing different spatial and temporal dynamics of those LUCC in the Portuguese territory. The main LUCC are related to reductions in forests and certain types of agricultural areas and increases in urban areas, but the main LUCC assume different dynamics when taken at the regional scale (NUTS II). Future tendencies of LUCC were also estimated using Cellular Automata-Markov (CA-Markov), and the results show the increasing and decreasing tendencies of the LUC types previously mentioned. The areas of LUC datasets with different properties were compared, and large area discrepancies were observed for some LUC classes. These assessments provide relevant results for the evaluation and understanding of LUCC for Portuguese planning processes in the near future.